Identity in Physics : A Historical, Philosophical, and Formal Analysis - French, Steven author 522403; Krause, Decio author 522404 (Oxford : Clarendon Press, 2006)
Steven French and Decio Krause examine the metaphysical foundations of quantum physics. They draw together historical, logical, and philosophical perspectives on the fundamental nature of quantum particles and offer new insights on a range of important issues. Focusing on the concepts of identity and individuality, the authors explore two alternative metaphysical views; according to one, quantum particles are no different from books, tables, and people in this respect; according to the other, they most certainly are. Each view comes with certain costs attached and after describing their origins in the history of quantum theory, the authors carefully consider whether these costs are worth bearing. Recent contributions to these discussions are analyzed in detail and the authors present their own original perspective on the issues. The final chapter suggests how this perspective can be taken forward in the context of quantum field theory.